Surfactant–polymer interactions: molecular architecture does matter1. Issue 12 (28th March 2015) - Banerjee, S.; Cazeneuve, C.; Baghdadli, N.; Ringeissen, S.; Leermakers, F. A. M.; Luengo, G. S.
<x xml:space="preserve">Abstract</x> There is a significant interest in understanding, at a molecular level, how the self-assembly of surfactant is affected by oppositely-charged polyelectrolytes (PEs). We use self-consistent field modeling and show that the modes of interaction of PEs strongly depend on the architecture of the PE on the segmental level.